Bride of the Shadow King - Mercedes, Sylvia (Mercedes, Sylvia. Bride of the Shadow King, 2024)
"The viral TikTok fantasy romance, now in a special print edition! An outcast princess makes a political marriage with a reluctant king to save both their kingdoms in this first book in the Bride of the Shadow King series-with an exclusive bonus scene, in print only! Though she is the oldest daughter, Princess Faraine lives in the background, shunned from court and kept out of sight. She's told her gods-gift makes her a liability to the crown, and has learned to give place to her beautiful, favored younger sister in all things. When the handsome and enigmatic Shadow King comes seeking a bride, Faraine is not surprised that her sister is his choice. Though not eager to take a human bride, King Vor is willing to do what is necessary for the sake of his people. When he meets the lively Princess Ilsevel, he quickly agrees to a marriage arrangement. So why can't he get the haunting eyes of her older sister out of his head?"--